Character association and path analysis studies for yield and morpho-biochemical characters in groundnut (Arachis hypogaea L.): Character association and path analysis studies for yield and morpho-biochemical characters in groundnut (Arachis hypogaea L.) - A M MISAL; V G SONAWANE; P L TAVADARE; D G SHINDE (Journal of Oilseeds Research, 2020)
The present investigation studies the extent of correlation among morpho-biochemical characters in 18 groundnut genotypes including three checks. The interrelationships were negative and significant for phenol content with leaf thickness and total sugar, whereas, positive and significant with trichome frequency and leaf water content. Trichome frequency, leaf thickness and jassid incidence exerted negative direct effect on pod yield at genotypic level. The components viz., trichome frequency through total sugar and thrips incidence; leaf thickness through SCMR, leaf water content, phenol content and total sugar; jassid incidence through leaf water content, SCMR, phenol content and leaf thickness exerted maximum negative indirect effect on pod yield.